Pemberdayaan Masyarakat Melalui Penyuluhan Inovasi Pengolahan Singkong Dan Opak Sebagai Upaya Pengembangan Produk Unggulan Di Desa Bleberan Kecamatan Jatirejo Kabupaten Mojokerto - Inuk Wahyuni Istiqomah; Angga Martha Mahendra (LP2M Institut Teknologi dan Bisnis Asia Malang, 2022)
The development of increasingly advanced technology and information at this time is still not fully understood by the community, especially among rural communities. This is indicated by the lack of innovation by residents on cassava and opaque food products which are abundant in their region which they do not realize what potential can be created from these food products. Food products Cassava and Opak are generally food products which are only processed into monotonous products such as tape, jemblem, blend, fried cassava and opaque crackers. So that people feel bored with various monotony of cassava, but on the other hand when processed into various variants of processed cassava well will have a positive impact on being a product that is quality, quality, competitive and of economic value. The community service program initiated by the Al-Anwar College of Economics aims to increase the knowledge and understanding of rural communities to have a high awareness of the concern for the use of abundant cassava from low value to competitive superior products. The methods of implementation are (1) community empowerment with innovation activities processed cassava raw materials, (2) counseling on the management of cassava into JEJUKO